What Makes a Citizen? Contemporary Immigration and the Boundaries of Citizenry. - Adem, Muna; Ambriz, Denise (Social Forces, 2023)
How do native-born Americans evaluate citizenship claims made by immigrant groups? Prior research identifies three broad patterns: respondents (1) make judgments based on immigrants' willingness to adhere to national norms and civic values, (2) rely on ethnoracial cues, and (3) rely on economic cues. Using a conjoint survey experiment, this is the first study to examine how these patterns hold across two distinct dimensions of citizenship—legal membership (being considered a citizen of the state) and cultural membership (being perceived as a fellow American). The results reveal that legal status and age of arrival are powerful determinants for attitudes toward legal membership. By contrast, ethnoracial boundaries have a more significant impact on cultural membership, even after accounting for key predictors, such as legal status and English proficiency. Moreover, we show that evaluations of citizenship claims differ for White and non-White Americans in meaningful ways. Compared to White respondents, Black and Latino respondents express higher levels of ingroup preference for legal membership, and Latinos are significantly more likely to use an inclusive definition of cultural membership. In tandem, these results highlight the importance of measuring citizenship as a multidimensional concept and the limitations of focusing on the dominant group to understand immigration attitudes in contemporary diverse societies.